THE EFFECT OF ISLAMIC APPEAL PROMOTIONAL STRATEGIES USED BY MULTINATIONAL BRANDS IN SAUDI ARABIA - Ghada Alghamdi; Manzar Ahmed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Many multinational companies identify Saudi Arabia as the leading business hub in the North Africa and Middle East. Multinational corporation or companies refer to multinational enterprises (MNEs) or foreign firms that conduct business in Saudi Arabia and whose parent organizations or corporations are located abroad. Multi-National Corporations could also include joint venture companies that are partly owned by businesspersons of Saudi Origin or Saudi government. Culture plays a principal role in influencing the market forces. This is not different in Saudi Arabia. Culture entails external effects that manipulate a consumer’s decision in a particular direction. Some of the principal components of culture include; belief, morals, knowledge, customs and any other habits influenced by the environment. In many instances, marketers find culture as a serious problematic and difficult to comprehend. Therefore, this study seeks to investigate the direct relationship between sales and Islamic appeal promotional campaigns by multinational brands in Saudi Arabia. This study used qualitative and quantitative approach to gather the primary data through interview and questionnaire survey. The obtained result reveals that Saudi consumers have minimal effect on their buying behavior due to religious endorsements in advertisements.